The Effect of the Problem-Based Learning Model Assisted by Assemblr Edu on the Mathematics Learning Outcomes of Students at SMP Negeri 2 Kabuh - Amiliya Hanim Nur Faidah; Oemi Noer Qomariyah (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
Low student achievement in three-dimensional geometry indicates the need for innovative instructional approaches that promote active participation and facilitate the visualization of abstract mathematical concepts. This study aimed to examine the effect of the Problem-Based Learning (PBL) model assisted by Assemblr Edu on the mathematics learning outcomes of students at SMP Negeri 2 Kabuh. A quantitative quasi-experimental approach with a nonequivalent posttest-only control group design was employed. Participants were selected through purposive sampling and comprised 64 ninth-grade students, with 32 students in the experimental class (IX-D) and 32 students in the control class (IX-C). Data were collected using a validated essay-based mathematics achievement test and analyzed through normality, homogeneity, and Mann–Whitney U tests using IBM SPSS Statistics version 27. The findings showed that the experimental group achieved a higher mean posttest score than the control group (88.68 vs. 74.84). The Mann–Whitney U test yielded p = .001, indicating a statistically significant difference in mathematics learning outcomes between the two groups. These findings demonstrate that PBL assisted by Assemblr Edu effectively supports students’ achievement in three-dimensional geometry by integrating problem-oriented learning with augmented reality-based visualization. This study contributes practical evidence that combining PBL with Assemblr Edu offers an effective technology-enhanced instructional alternative for improving mathematics learning outcomes at the junior secondary school level.